2011
DOI: 10.1073/pnas.1107912108
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear membranes control symbiotic calcium signaling of legumes

Abstract: Nuclear-associated oscillations in calcium act as a secondary messenger in the symbiotic signaling pathway of legumes. These are decoded by a nuclear-localized calcium and calmodulin-dependent protein kinase, the activation of which is sufficient to drive downstream responses. This implies that the calcium oscillations within the nucleus are the predominant signals for legume symbiosis. However, the mechanisms that allow targeted release of calcium in the nuclear region have not been defined. Here we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
177
0
9

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 193 publications
(193 citation statements)
references
References 38 publications
7
177
0
9
Order By: Relevance
“…In animal systems, some Ca 2+ -gated K + channels are voltage gated, but the lack of voltage sensor motifs in the transmembrane domain of DMI1 suggests that changes in voltage would have no effect on the conductance of DMI1. The Ca 2+ pump is modeled to represent MCA8, a SERCA-type Ca 2+ ATPase (Capoen et al, 2011), and it resequesters the released Ca 2+ into the Ca 2+ store against the concentration gradient. In this model, DMI1 is presumed to be able to change the membrane voltage to provide a counterion current to the Ca 2+ movement.…”
Section: Assumptions Made To Model Ca 2+ Behaviormentioning
confidence: 99%
See 4 more Smart Citations
“…In animal systems, some Ca 2+ -gated K + channels are voltage gated, but the lack of voltage sensor motifs in the transmembrane domain of DMI1 suggests that changes in voltage would have no effect on the conductance of DMI1. The Ca 2+ pump is modeled to represent MCA8, a SERCA-type Ca 2+ ATPase (Capoen et al, 2011), and it resequesters the released Ca 2+ into the Ca 2+ store against the concentration gradient. In this model, DMI1 is presumed to be able to change the membrane voltage to provide a counterion current to the Ca 2+ movement.…”
Section: Assumptions Made To Model Ca 2+ Behaviormentioning
confidence: 99%
“…The pumps are needed to resequester Ca 2+ after each release event, actively transporting Ca 2+ against the concentration gradient using ATP. A recent study found a SERCA-type Ca 2+ ATPase, MCA8, that is located on the inner and outer nuclear envelope of M. truncatula and is required for the symbiotic Ca 2+ oscillations (Capoen et al, 2011). Such SERCA pumps are widely distributed on plant membranes, and the variation in their structure points to them being differentially regulated (Sze et al, 2000).…”
mentioning
confidence: 99%
See 3 more Smart Citations